Association of urinary metabolites of polycyclic aromatic hydrocarbons with urinary incontinence in adults: A cross-sectional study - ChunXiang Bao; Jie Luo; ShuYing Miao (Heliyon)
This study aims to investigate the association between polycyclic aromatic hydrocarbon (PAH) metabolites and urinary incontinence (UI) in the general adult population. This study analyzed six urinary PAH metabolites in the general adult population from the 2005–2016 National Health and Nutrition Examination Survey (NHANES). UI was distinguished into stress UI (SUI), urgency UI (UUI), mixed UI (MUI), and any UI by self-reported questionnaires. Multiple logistic regression, restricted cubic spline (RCS) regression, and quantile g-computation (QG-C) were applied to assess the association between PAHs (individual and mixture exposure) and the prevalence of UI. A total of 8,136 participants were included in our study. The participants had a median age of 45.9 years, and 48.7 % of individuals were female. Most ln-transformed PAHs were positively and linearly related to the prevalence of SUI and any UI in women (P < 0.05). Increasing prevalence of SUI was associated with the highest quantiles of 3-hydroxyfluorene (3-FLU) (OR = 1.72, 95%CI = 1.27–2.33, P for trend = 0.002), 2-hydroxyfluorene (2-FLU) (OR = 1.75, 95%CI = 1.29–2.38, P for trend = 0.008), and 1-hydroxypyrene (1-PYR) (OR = 1.44, 95%CI = 1.05–1.96, P for trend = 0.012) compared with the lowest quantiles in women. The mixture of urinary PAH metabolites was significantly associated with an increased prevalence of SUI (OR = 1.09, 95%CI: 1.01–1.19, P = 0.038) in women. Urinary 2-FLU had the greatest positive contribution to the overall effect, while 2-hydroxynapthalene (2-NAP) was the major negative contributor. Our study demonstrated that mixture exposure to PAHs is associated with the prevalence of SUI in adult women, which might be primarily driven by 2-FLU.